SCIENTIFIC KNOWLEDGE: ITS ESSENCE, CORE PRINCIPLES, AND ROLE IN INNOVATIVE ACTIVITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article reveals that scientific knowledge is one of the continuous and complex processes of human thought. It examines how scientific knowledge manifests itself as the most important instrument for human understanding of the surrounding environment, society, and oneself, and analyzes how, in this process, a person assimilates new information through experience, observation, and analysis, then generalizes it to form new concepts. It is argued that scientific knowledge, grounded in the principles of objectivity, validity, logical consistency, and systematicity, enriches existing knowledge and opens pathways to new discoveries. Accordingly, the article contends that scientific knowledge is not merely a means of acquiring knowledge, but also one of the most important factors ensuring the intellectual and spiritual development of humanity.